Molecular Cloning and Expression of a Thermostable Α-Amylase from Geobacillus Sp. - Kassaye, Elias Kebede (2009)
Starch degrading enzymes like amylase have received great deal of attention because of their perceived technological significance and economic benefits. Selection of a suitable strain is the most significant factor in the amylase production process. On the other hand the screening for a single amylase is difficult because one strain can produce different amylases with different specificities or the amount of amylase produced may be very low. Thus the cloning of one gene directing the synthesis of the desired amylase in a well characterized host like E. coli should help greatly in the characterization of new amylases and also allow a significant yield increase. Studies on the screening of amylase producing bacterial strains were carried out on soil and water samples collected from a hot spring located in Slim River, Perak, Malaysia. The bacteria were cultivated in a mineral medium containing soluble starch as the sole carbon source. Three of the isolates namely SR37, SR41, SR74 have demonstrated good activity based on the assay performed using DNS method at 60oC and pH 7.0. The isolates showed activity of 2.44 U/ml, 4.5 U/ml, 2.05 U/ml for amylopectin and 1.78 U/ml, 3.54 U/ml, 1.65 U/ml for soluble starch, respectively. None of the isolates except SR74 (1.65 U/ml) showed activity at 70oC. Since it showed activity at 70oC, further study was conducted on the isolate SR74 for identification, gene cloning, sequencing and expression for the α-amylase enzyme. Gram staining and morphological studies revealed the isolate was a Gram positive Bacillus. Molecular characterization using the 16S rDNA for the isolate SR74 revealed the organism closely related to the members of the genus Geobacillus. The fatty acid methyl ester analysis using the Sherlock system also resulted in a typical fatty acid profile of a thermophilic Geobacillus and other bacilli. Among them the iso-branched pentadecanoic acid (iso-15:0), haxadecanoic acid (iso-16:0) and heptadecanoic acids ( iso-17:0) accounted for 82.26% of the total fatty acids.Iso-15:0 and iso-17:0 were especially abundant. This isolate exhibited anteiso-15:0 (1.05%) and anteiso-17:0 (6.5%) as minor components (7.55% of the total). The isolate was identified as Geobacillus sp. SR74. The gene coding for a thermostable α-amylase from Geobacillus sp. SR74 was isolated, sequenced and expressed in Escherichia coli BL21 (DE3) pLysS. Gene sequencing showed that the enzyme secreted by this isolate shared 98% similarity with Geobacillus stearothermophilus α-amylase gene. The ORF of the gene codes for 549 amino acids. The signal peptide comprised 34 amino acids and the remaining 515 amino acids belong to the mature polypeptide. The region encoding the mature α- amylase was heterogeneously expressed in E. coli BL21 (DE3) pLysS cells using the pET-32b expression system under the control of the T7 promoter. The mature enzyme had a theoretical molecular weight of 58,547 Daltons and a theoretical pI of 5.61. Optimization studies revealed that the highest enzyme activity was obtained at 16h post induction (32.414 U/ml). The optimum inducer concentration was found to be 0.15mMol L-1 IPTG (39.73 U/ml). With regard to production media, LB (49.53 U/ml) and 0.75YT (51.06 U/ml) were found to be best for optimum production of the recombinant enzyme, while the A600nm of 0.75 (58.3 U/ml) being the best microbial density for inducing the production of the enzyme.